Comparison the effectiveness of compassion and acceptance and commitment training (act) on psychological well-being - Soleimanpour Moghaddam, Hosein; Saiedi, Ali; Mahdian, Hossein (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of the present study is comparison the effectiveness of compassion and acceptance and commitment rtraining (act) on psychological well-being. Method: This study was quasi-experimental with a pre-test and post-test design with control group. Research population consisted of 11th grade students in four districts of Mashhad in 2021-22 academic years. From schools that had at least 4 classrooms of 11th grade, one school were selected by cluster sampling. After visiting that school, three classes were randomly selected and divided lnto three equal groups.the experimental groups recieved 8 sessions of 90 minutes separately, with methods of the compassion and aecep tance and cammi tment - based training (act) and the control group didnot receive training.Research tools was pschological well-being scale (Ryff,1989). Data were analyzed with univaiate analysis of variance, with repeated measures and Bonferroni hoc methods using SPSS-25. Results: Results indicated the effectiveness of both methods, compassion and acceptance and commitment training (act), in increasing psychological well-being was (P˂0/001). Also was no significant difference between methods in increasing pschological well-being (P > 0/05). Conclusion: According to the findings of the present study, to increase pschological well-being for students,methods of compassion and acceptance and commitment training can be used.